Biomedical applications of aromatic azo compounds - Ali, Yousaf; Abd Hamid, Shafida; Rashid, Umer (Bentham Science, 2018)
Azo dyes are widely used in textile, fiber, cosmetic, leather, paint and printing industries. Besides their characteristic coloring function, azo compounds are reported as antibacterial, antiviral, antifungal and cytotoxic agents. They have the ability to be used as drug carriers, either by acting as a ‘cargo’ that entrap therapeutic agents or by prodrug approach. The drug is released by internal or external stimuli in the region of interest, as observed in colon-targeted drug delivery. Besides drug-like and drug carrier properties, a number of azo dyes are used in cellular staining to visualize cellular components and metabolic processes. However, the biological significance of azo compounds, especially in cancer chemotherapy, is still in its infancy. This may be linked to early findings that declared azo compounds as one of the possible causes of cancer and mutagenesis. Currently, researchers are screening the aromatic azo compounds for their potential biomedical use, including cancer diagnosis and therapy. In this review, we highlight the medical applications of azo compounds, particularly related to cancer research. The biomedical significance of cis-trans interchange and negative implications of azo compounds are also discussed in brief.